One-pot synthesis of 3-hydroxyanthranilate derivatives using furans, bromoalkyne, and secondary amines. Issue 19 (6th May 2015) - Shinohara, Hiroyuki; Sonoda, Motohiro; Hayagane, Naoya; Kita, Shota; Okushima, Shunsuke; Tanimori, Shinji; Ogawa, Akiya
Graphical abstract: Abstract: A novel and convenient method for synthesizing 3-hydroxyanthranilate derivatives using furans, methyl 3-bromopropiolate, and secondary amines was developed. The synthetic reaction consisted of four steps: the Diels–Alder reaction, a conjugate addition reaction, dehydrobromination, and a ring-opening aromatization reaction. A plausible reaction pathway is described on the basis of the structures of the reaction intermediates. By using this method, sterically hindered 3-hydroxyanthranilate derivatives could be obtained selectively in good yields for four-steps.